Adolescents With ADHD Do Not Take Longer to Recover From Concussion - Cook, Nathan E.; Iverson, Grant L.; Maxwell, Bruce; Zafonte, Ross; Berkner, Paul D. (Frontiers in Pediatrics, 2021)
The objective of this study was to determine whether adolescents with attention-deficit/hyperactivity disorder (ADHD) have prolonged return to school and sports following concussion compared to those without ADHD and whether medication status or concussion history are associated with recovery time. We hypothesized that having ADHD would not be associated with longer recovery time. This prospective observational cohort study, conducted between 2014 and 2019, examined concussion recovery among school sponsored athletics throughout Maine, USA. The sample included 623 adolescents, ages 14-19 (M=16.3, SD=1.3 years), 43.8% girls, and 90 (14.4%) reported having ADHD. Concussions were identified by certified athletic trainers. We computed days to return to school (full time without accommodations) and days to return to sports (completed return to play protocol) following concussion. Adolescents with ADHD (median days=7, IQR 3-13, range 0-45) did not take longer than those without ADHD (median days=7, IQR 3-13, range 0-231) to return to school (U=22,642.0, p=.81, r=.01; Log Rank: χ2 (1)=.059, p=.81). Adolescents with ADHD (median days=14, IQR 10-20, range 2-80) did not take longer than those without ADHD (median days=15, IQR 10-21, range 1-210) to return to sports (U=20,295.0, p=.38, r=.04; Log Rank: χ2 (1)=.511, p=.48). Medication status and concussion history were not associated with longer recovery times. Adolescents with ADHD did not take longer to functionally recover following concussion. Recovery times did not differ based on whether adolescents with ADHD reported taking medication to treat their ADHD or whether they reported a prior history of concussion.